Perancangan Unit Instalasi Pengolahan Air Bersih Untuk Kebutuhan Kampus Universitas Panca Bhakti - Anggraini, Ika Muthya; Gunawan, Ivan Andri; Rahsia, Shandra Andina (Universitas Tanjungpura, 2025)
Clean water is a fundamental necessity that plays a vital role in supporting various activities within higher education institutions, including Universitas Panca Bhakti (UPB). The availability of clean water that meets quality standards is essential to sustain academic activities, sanitation, laboratory work, and campus facility maintenance. However, the current condition shows that the existing water quality does not comply with the quality standards stipulated in the Indonesian Ministry of Health Regulation No. 2 of 2023. Therefore, a more reliable water treatment system is required. This study aims to design an adaptive and energy-efficient Clean Water Treatment Plant (CWTP) tailored to the characteristics of UPB